2018
DOI: 10.1176/appi.ps.201800067
|View full text |Cite
|
Sign up to set email alerts
|

Racial-Ethnic Disparities in First-Episode Psychosis Treatment Outcomes From the RAISE-ETP Study

Abstract: In usual community care, non-Hispanic blacks scored higher on measures of psychiatric symptoms and were less likely to receive important services, compared with non-Hispanic whites. In NAVIGATE, racial and ethnic differences in psychiatric symptoms were not evident, although non-Hispanic blacks were less likely than non-Hispanic whites to receive family psychoeducation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 43 publications
(37 reference statements)
0
40
0
Order By: Relevance
“…Our findings are also relevant to international policies on mental health. For example, a widespread of early psychosis services in the United States is ongoing therefore; deploying early psychosis service with a whole community approach (set out earlier) in mind will be effective in meeting the needs of those who need such services the most, as well as addressing ethnic disparities in psychosis outcomes [ 61 ]. A long duration of untreated psychosis is also a reflection of an onset that goes unnoticed because the person has limited social network.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also relevant to international policies on mental health. For example, a widespread of early psychosis services in the United States is ongoing therefore; deploying early psychosis service with a whole community approach (set out earlier) in mind will be effective in meeting the needs of those who need such services the most, as well as addressing ethnic disparities in psychosis outcomes [ 61 ]. A long duration of untreated psychosis is also a reflection of an onset that goes unnoticed because the person has limited social network.…”
Section: Discussionmentioning
confidence: 99%
“…One strength of the sample was its representation of gender diversity, as nearly a fifth of the sample identifying as non-binary, and one in ten identifying as transgender. While our study provides a starting point to understand overall trends for young adults with EP, development and dissemination work should also incorporate insights from studies focused in-depth on the experiences of underrepresented groups, particularly considering racial-ethnic service disparities in both specialty and community care for psychosis (Oluwoye et al, 2018 ). Our results are also limited by the lack of a non-EP comparison group; thus, they cannot speak to whether the preferences identified here for individuals with early psychosis differ from those of young adults with other mental health symptoms or in the non-clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…17 18 For instance, in a large clustered randomised trial of NAVIGATE, a CSC programme for FEP, 69% of family members did not participate in family psychoeducation and only 29% attended five or more appointments. 19 20 These findings also revealed that racial/ethnic minority families engaged in treatment at lower rates than non-Hispanic whites. 19 We need to better understand and systematically address factors and underlying mechanisms that affect the successful implementation of family-based interventions in mental health settings.…”
Section: Introductionmentioning
confidence: 89%
“…Based on previously collected and published data that informed IM step 1 (problem analysis), 19 SDT was chosen as an overarching theoretical framework to ensure that the intervention’s underlining mechanism of motivation is targeted by incorporating specific components, such as motivational statements, an approach consistent with IM step 2 (review of theory-based methods and practical strategies). 56 SDT focuses on three fundamental human needs: autonomy (choice), competence (self-efficacy) and relatedness (belonging).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation